?STUDIES ON GERMINATING CARUM CAPTICUM SEED LIPIDS (Biological Sciences - PJSIR, 2022)
Studies have been carried out on germinated seeds of Carum capticum for the determination of different lipid classes, (8.5 -15.0% and 12.4 -18.2%) in cotyledons and roots respectively by the application of thin layer chromatog- raphy. Each lipid class was hydrolysed, methylated and purified consequently to find out the fatty acid composition ranging C12,o -C20,o by the use of gas liquid chromatography.